Penggunaan foto udara untuk penilaian frosi tanah dengan menggunakan pendekatan geomorfologi di ubderah aliran sungai lesti hulu Malang - Jawa Timur - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
A study of aerial photograph application for assesment of erosion rate was carried out on Lesti Upper Sub Watershed. The aim of this study is to know the application of aerial photograph for assesment of soil erosion by geomorphological approach on studied area The study started by aerial photo-interpretation to obtain geomorphological unit, followed by interpretation on land characteristics such as slope, vegetation and land use, and erosion features. Field study was carried out to test and complete aerial photo-interpretation and to obtain data which can not be obtained by aerial photo interpretation such as rainfall and the characteristics of soils and rocks. Reinterpretation were needed to correct aerial photo-interpretation at first step. The result of this study showed that landform units on studied area are dominated by volcanic origin such as crater, cone, upper slope, middle slope and lower slope, whereas fluvial origin accupy smallest area Soil susceptibility to erosion range from slightly susceptible to extremely high susceptibility to erosion. Landform from volcanic origin are dominated by highly susceptible to extremely high susceptibility to erosion, whereas landform from fluvial origin are slightly susceptible and moderate susceptible to erosion.